Kefahaman Kemahiran Saintifik Dalam Kalangan Guru Pelatih Program Persediaan Ijazah Sarjana Muda Perguruan (PPISMP) Opsyen Pendidikan Awal Kanak-Kanak (PAKK) - Thomas @ Tupang, Lina binti (Selangor Humaniora Review, 2018)
Science skills is an important aspect in learning Science. The ability to understand the two components of science skills that is, Science Process Skills and Manipulative Skills can increase students’ grasp of science knowledge. Thus the aim of this study is to measure the level of understanding of science process skills and manipulative skills among 14 teacher trainees undergoing a Preparatory Programme for the Bachelor in Teaching Degree (Early Childhood Education) at a teacher training institute in Tawau, Sabah. The level of understanding is measured by using the Science Process Skills Closed Ended Question (SJTKPS) and the Manipulative Skills Closed Ended Questions (SJTKM). To support the findings from the two instruments mentioned, three teacher trainees were interviewed. Both instruments were used after the teacher trainees have gone through four science activities prepared by the researcher. Descriptive statistical analysis in the form of percentage and frequency is used to analyse data. The findings show that three (25%) of the science process skills were mastered at the level of excellent; four (33%) good and five (43%) marked at moderate. For the manipulative skills, one (20%) was at the moderate level, while 3 (60%) did not master the skill. The high percentage at the moderate level for science process skills and the weak level for manipulative skills indicates that the respondents in this research have not fully mastered the science skills. As a result, the science process skills and manipulative skills need to be stressed upon in the teaching and learning objectives of the Science Curriculum in order to produce teachers who not only have knowledge of Science and Technology but also able to apply existing knowledge.